2018
DOI: 10.1111/eos.12418
|View full text |Cite
|
Sign up to set email alerts
|

Tooth formation and eruption – lessons learnt from cleidocranial dysplasia

Abstract: The principles of formation, renewal, and eruption of teeth are discussed. Numerous genetic aberrations may affect the formation and eruption of teeth. Cleidocranial dysplasia (CCD), caused by mutations in the runt-related transcription factor 2 (RUNX2) gene, is such a condition. The dental phenotype includes problems in both tooth formation (multiple supernumerary permanent teeth) and tooth eruption (lack of shedding of primary teeth and delayed or arrested eruption of permanent teeth). Clinical studies, anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 46 publications
1
41
0
8
Order By: Relevance
“…The case report shows clinical and radiographic characteristics similar to the classic pictures of Cleidocranial Dysplasia, as described in the literature (El-gharbawy et al, 2011;Jaruga et al,2016;Kreiborg et al, 2018;Lu et al, 2015;Porciuncula et al, 2013). The patient does not only present the pathognomonic triad, but also other phenotypic characteristics common to patients with the syndrome.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The case report shows clinical and radiographic characteristics similar to the classic pictures of Cleidocranial Dysplasia, as described in the literature (El-gharbawy et al, 2011;Jaruga et al,2016;Kreiborg et al, 2018;Lu et al, 2015;Porciuncula et al, 2013). The patient does not only present the pathognomonic triad, but also other phenotypic characteristics common to patients with the syndrome.…”
Section: Resultssupporting
confidence: 73%
“…Bilateral clavicular agenesis is a rare manifestation, corresponding to 10% of cases, and allows hypermobility from the shoulders to the midline. Additionally, individuals affected by the syndrome may have short stature, pectus excavatum, valgus knees, scoliosis, defects in long bones, defects in the bones of the fingers, hypoplastic or absent nails, delay in the union of the mandibular symphysis, relative mandibular prognathism, arched, narrow and deep palate, and dental anomalies such as enamel hypoplasia, supernumerary teeth, ectopic dental location, non-eruption, and abnormal morphology, mainly radicular, of permanent teeth and prolonged retention of primary Research, Society and Development, v. 9, n. 9, e916998052, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.8052 dentition (El-gharbawy et al, 2011;Jaruga et al, 2016;Kreiborg et al, 2018;Lu et al, 2015;Mundlos et al, 1995;. Nevertheless, clinical manifestations and intensity may vary between affected patients due to the variable expressiveness of the syndrome (Elgharbawy et al, 2011;Lu et al, 2015;Porciuncula et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was suggested that supernumerary teeth result from the rescue of the third dentition’s regression in humans [ 49 – 51 ]. Radiographic examination of tooth development in patients with cleidocranial dysplasia performed over several years suggests that a part of the third dentition may cause the condition [ 52 ]. Clinical criteria for supernumerary teeth derived from the third dentition are as follows: (1) the supernumerary tooth is located on the lingual side of permanent teeth, (2) the supernumerary tooth develops after permanent teeth formation, and (3) the shape of the supernumerary tooth is similar to that of the preceding teeth [ 53 , 54 ].…”
Section: Main Textmentioning
confidence: 99%
“…The eruption failure cannot be classified based only on clinical characters, but the mechanism by which this pathological condition occurs, including possible physical and/or biological defects in the eruption process, should be considered and investigated [ 3 ]. Eruption disorders are in general difficult to diagnose given the scarce studies on the eruptive process [ 4 ]. Therefore, the better understanding of the pathogenic conditions and disorders derived from eruption failure depends on a complete understanding of the specific molecular mechanisms underlying normal eruption [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%